THE EVOLVING ROLE OF TEACHERS IN BLENDED LEARNING FROM INSTRUCTORS TO FACILITATORS - Shahina Shukhratova (TADQIQOTLAR, 2025)
Abstract The rapid integration of technology in education has transformed the traditional role of teachers, particularly in blended learning environments. This article explores the evolving role of teachers from instructors to facilitators in blended learning settings. By  examining  key  methodological  aspects,  this  study  highlights  the  importance  of adaptability,  engagement,  and  collaborative  learning.  The  findings  indicate  that  as teachers transition to facilitators, they enhance student autonomy and foster a more interactive  learning  environment.  This  paper  provides  insights  for  educators  and institutions aiming to optimize blended learning experiences.